Unravelling the potential of digital servitization in sustainability-oriented organizational performance: Does digital leadership make it different? - Huy Quang Pham; Phuc Kien Vu (Economies, 2022)
This research proposed and enhanced a statistically reliable paradigm for determining the impacts of the role of digital servitization (DS) as a potential facilitator of sustainable and smart service innovation ecosystem (SSSIE) establishment and sustainability-oriented organizational performance (SOOP) improvement. Additionally, this research aimed to cast light on the role of digital leadership (DL) as a moderator of the hypothesized model. Structural equation modeling and multigroup analysis (MGA) were employed to process and analyze the data procured from a cross-sectional convenience sample of 412 respondents representing various public service sector organizations (PSSOs). The statistical outcomes corroborated that DS was positively and significantly correlated to SSSIE establishment, and at the same time, SOOP was significantly intensified by DS and SSSIE. Next, the nexus between DS and SOOP was enhanced when SSSIE was operationalized. Lastly, the MGA outcomes confirmed that all of the coefficients in the proposed model were statistically significantly different under the moderating effect of DL. These obtained findings could bring numerous valuable in-depth insights for practitioners and policymakers in digital initiatives management and governance.
Keywords: 330; digital servitization; innovation ecosystem; organizational performance; public service sector organization